Corporate Social Responsibility (CSR) Sebagai Tanggung Jawab Sosial - Nurasiah Harahap (Universitas Islam Sumatera Utara, 2018)
Every company or cooperation is obligatory to carry out social and environmental responsibility. Corporate Social Responsibility (CSR) is regulated in Article 1 paragraph 3 of Law no. 40 of 2007 on Limited Liability Company which reads: